2021
DOI: 10.1007/s00704-021-03654-5
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of empirical equations for estimating reference evapotranspiration in different climates of Iran

Abstract: The accurate estimation of reference evapotranspiration (ETref) is a crucial component for modeling hydrological and ecological cycles. The goal of this study was the calibration of 32 empirical equations used to determine ETref in the three classes of temperature-based, solar radiation-based and mass transfer-based evapotranspiration. The calibration was based on measurements taken between the years 1990 and 2019 at 41 synoptic stations located in very dry, dry, semidry and humid climates of Iran. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…According to Sharafi and Ghaleni's (2021a) results, the ET ref were estimated by empirical equations of the PM-FAO 56 for very dry climate, the Hargreaves equation for the semidry climate, and the Penman 1 and 2 equations for the dry and humid climates, respectively (Table 1). At the same time, the Penman-Monteith method is a suitable method in most parts of the country due to its comprehensiveness (Sharafi and Ghalenee, 2021b).…”
Section: Et Ref Evaluationmentioning
confidence: 99%
“…According to Sharafi and Ghaleni's (2021a) results, the ET ref were estimated by empirical equations of the PM-FAO 56 for very dry climate, the Hargreaves equation for the semidry climate, and the Penman 1 and 2 equations for the dry and humid climates, respectively (Table 1). At the same time, the Penman-Monteith method is a suitable method in most parts of the country due to its comprehensiveness (Sharafi and Ghalenee, 2021b).…”
Section: Et Ref Evaluationmentioning
confidence: 99%
“…Furthermore, they concluded that radiation-based equations are best suited to estimate ET 0 in the study region. Also, Tabari et al (2013) and Sharafi and Ghaleni (2021) concluded that the radiation-based models were the best-suited equations, while mass transfer-based equations had the worst performances in Iran. Tabari et al (2012) found the Ritchie equation gives an acceptable performance in modelling crop ET Tabriz, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…They are listed in Table 2 where Equations (4)–(14), (15)–(24), and (25)–(34) are temperature‐, radiation‐, and mass‐transfer‐based equations, respectively. This bundle of equations is widely and commonly used to estimate ET 0 empirically for different climates and regions (Sharafi and Ghaleni, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, establishing these stations can be expensive, particularly in developing countries. The Penman-Monteith equation based on FAO 56 (PM-FAO 56 ) has typically been used as a semi-empirical equation for prediction of ET ref [ [12] , [13] , [14] , [15] ]. In spite of the acceptance of the PM-FAO 56 equation, it requires full datasets of climatic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers studied and evaluated so far ET ref models in various climates [ 15 , [17] , [18] , [19] , [20] ]. The empirical models are usually divided into four categories: models based on temperature, radiation and mass transfer as well as a combination of various models [ 6 , 14 , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%